Seasonal Variation in the Physiological Response of Atlantic Cod ( Gadus morhua ) to Low Salinity - Dutil, J.-D.; Munro, J.; Audet, C.; Besner, M. (Canadian Journal of Fisheries and Aquatic Sciences, 1992)
Plasma Na + , Cl − , K + , osmotic pressure, Cortisol, glucose, and protein, blood hemoglobin and hematocrit, and water content of skeletal muscle were measured at regular intervals during a 28-d period following the transfer of Atlantic cod (Gadus morhua) to waters of 7, 14, 21, and 28‰ (control) salinity. These experiments were repeated four times at 3-mo intervals under natural photoperiod and temperatures (0–10 °C). Exposure to 7‰ salinity caused large decreases in plasma Na + in winter (25 mmol/L over 14 d) and in spring (32 mmol/L over 7 d) when the lowest value for the year was reached (156 mmol/L). Transfer to 14 and 21‰ salinity resulted in a slight decrease (maximum 4%) in plasma Na + which was much smaller than the seasonal variation (14%) observed in controls. Hydration of skeletal muscle occurred only at 7‰ (2.3% maximum), but these changes were small compared with the seasonal variation (3.9%) observed in the controls. Principal components and clustering analyses showed that all ionic and osmotic variables measured were highly correlated while being only weakly associated with the condition or reproductive status of the fish. There were no indications that acclimation to low salinity was stressful for cod.